2012
DOI: 10.1177/0004867411427807
|View full text |Cite
|
Sign up to set email alerts
|

The impact of gender on early ill-health retirement in people with heart disease and depression

Abstract: Ill-health retirement is common in those with heart disease. Women appear to be particularly susceptible to the effects of comorbid depression. Given the policy emphasis on reducing the number of people leaving the workforce early, women with early heart disease may represent a particular group in whom interventions designed to detect and treat comorbid depression should be targeted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 37 publications
1
11
1
Order By: Relevance
“…The gender effect on return to work has been seen elsewhere in Australia where the impact of prior illness was more pronounced upon ill-health-retirement in women than men [28]. This raises the question of how to engage women with chronic illnesses in workforce participation when such policies and programmes may be biased towards male roles and expectations.…”
Section: Discussionmentioning
confidence: 97%
“…The gender effect on return to work has been seen elsewhere in Australia where the impact of prior illness was more pronounced upon ill-health-retirement in women than men [28]. This raises the question of how to engage women with chronic illnesses in workforce participation when such policies and programmes may be biased towards male roles and expectations.…”
Section: Discussionmentioning
confidence: 97%
“…Previous evidence also suggests that ill‐health tends to have a larger effect on the labour market participation of men than women (see Kalwij and Vermeulen ; Paradise et al . ; Pit et al . ).…”
Section: Data and Methodological Approachmentioning
confidence: 99%
“…Paradise et al used data from the 45 and Up Study to examine the association of heart disease, depression and ill-health retirement in a large community sample. 25 The authors found that a prior diagnosis of depression was associated with a three-fold increase in the risk of ill-health retirement. 25 Schofield et al developed a microsimulation model of health and disability and found that individuals who retired early due to a diagnosis of depression had an income that was 73% lower than their full-time employed counterparts.…”
Section: Earlier Retirementmentioning
confidence: 99%
“…25 The authors found that a prior diagnosis of depression was associated with a three-fold increase in the risk of ill-health retirement. 25 Schofield et al developed a microsimulation model of health and disability and found that individuals who retired early due to a diagnosis of depression had an income that was 73% lower than their full-time employed counterparts. 19 Schofield et al estimated the national cost of this early retirement at A$278 million (A$367 million in 2015) in lost income taxation revenue, A$407 million (A$537 million in 2015) in additional transfer payments and around A$1.7 billion (A$2.2 billion in 2015) in gross domestic product.…”
Section: Earlier Retirementmentioning
confidence: 99%